Preparation of Biosorbent from Kapok Fruit Peel (Ceiba pentandra) for Adsorption of Lead Waste - Eddy Heraldy; Novia Purnamawati; Yuniawan Hidayat; Khoirina Dwi Noegrahaningtyas; Idul Fitri Nurcahyo (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
The preparation of biosorbent from kapok fruit peel (KBK) for lead (Pb(II)) removal was conducted mechanically by expanding the surface of the biosorbent and activating KBK with the addition of 1 M HCl for 20 minutes. The effect of activation on increasing the number of active groups and the number of pores in the biosorbent was proven by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The FTIR data showed a shift and an increase in wavenumber intensities of active adsorbent groups such as -OH and -C=O. The SEM data revealed that the morphology of the adsorbent increased in the number of pores that appeared rough and irregular. The Pb(II) adsorption treatment used a batch method at pH 2–5, contact time of 0–120 minutes, and adsorbate concentration of 10–50 ppm. The adsorption of Pb(II) ions reached optimum conditions at pH 4 and a contact time of 60 minutes, with an adsorption capacity of 6.9522 mg/g and an adsorption rate of 98.71%. Adsorption data showed that Pb(II) ions uptake to KBK biosorbent followed the Langmuir isotherm model equation and pseudo-second-order kinetic model. The adsorption capacity of activated KBK is greater than that of non-activated KBK.